Towards an Understanding of the Role of VGF-Derived Peptides - Ashford, Toni Winona Marie (2021)
Pro-VGF, a product of the vgf gene, is expressed in abundance in neuronal and neuroendocrine cells, including the β cells of the islet of Langerhans. Post translational endoproteolytic processing of pro-VGF results in formation of several biologically active peptides, which are secreted in response to different stimuli and have been shown to have various physiological roles including glycaemic control, memory and learning.